Efecto de la fertilización orgánica e inorgánica sobre el crecimiento de tomate (solanum lycopersicum) en ambientes protegidos (Agroindustria, Sociedad y Ambiente, 2018)
The tomato (Solanum lycopersicum) is one of the vegetables with the highest production in the world, to maintain its yields it is necessary improve fertilization to soil, so it is necessary that fertilizers supply the nutrients required by the plants, for this reason the effect of different treatments of organic and inorganic fertilization on the growth of tomato plants was evaluated, for this a research was conducted at greenhouse level, a completely randomized experiment was carried out, where the effect of 5 treatments was evaluated: (T0) control, (T1) inorganic fertilization, (T2) compost, (T3) vermicompost, (T4) compost + vermicompost, which were replicated 5 times for 25 experimental units. During the crop cycle, biometric variables were evaluated: plant height, number of leaves, stem diameter and changes in edaphic variables: organic matter, phosphorus, potassium, calcium, magnesium, electrical conductivity and pH. The statistical analysis was carried out applying a variance analysis and DGC grouping with a probability value p
Keywords: Agroecology; fertility; horticulture; sustainability; vermicompost